Gendered decision making and adaptation to climate change in Mt. Elgon Region, Eastern Uganda - Bomuhangi, Allan; Nabanoga, Gorettie; Namaalwa, Justine J.; Jacobson, Michael G.; Gombya-Ssembajjwe, W. (2016)
This study investigates intra household level decision-making in two rural districts in the Mt Elgon region. Data was collected from 442 respondents using a household survey. Pearson Chi-Square ( 2), Multinomial and logistic regressions were used to understand the gender dimensions of decision making and barriers to climate change adaptation. The study demonstrates that coping and adaptation decisions within households are undertaken either as sole or joint decisions. Sole decisions are made either by the husband or by the wife while joint decisions are made by the husband and wife together or with other household members. However, most coping and adaptation decisions were often made either by the husband or by both the husband and wife. Seldom were decisions made individually by the wife or jointly with other household members. The study concludes that men or women may make decisions on certain coping and adaptation practices and not others implying that the kinds of coping and or adaptation practices will also determine who makes decisions.